A Case of Rectal Dieulafoy’s Ulcer and Successful Endoscopic Band Ligation - Yukako Yoshikumi; Hirosato Mashima; Junko Suzuki; Yutaka Yamaji; Makoto Okamoto; Keiji Ogura; Takao Kawabe; Masao Omata (Canadian Journal of Gastroenterology)
Dieulafoy’s ulcer is a rare cause of gastrointestinal bleeding. The lesion is usually located in the stomach, although it may occur anywhere in the gastrointestinal tract. A 44-year-old man was admitted to hospital due to cerebral infarction. On the 23rd day of hospitalization, he showed massive hematochezia. He underwent an urgent colonoscopy. There was a visible protuberant vessel without significant ulceration at the fundus of the rectum, consistent with a Dieulafoy’s ulcer. It was treated by endoscopic hemoclipping. However, rebleeding occurred three times despite repeated hemoclipping. Finally, endoscopic band ligation was successfully performed to achieve permanent hemostasis. Endoscopic band ligation is an effective treatment for bleeding rectal Dieulafoy’s ulcer.